PENGELASAN BAJA HADFIELD TERHADAP BAJA KARBON DAN ANALISIS PENGARUH PARAMETER PENGELASAN TERHADAP KARAKTERISTIK HASIL LASAN - Sonawan , Hery
Abstract : In welding dissimilar metals, an optimum joint characteristics can be obtained with proper chooice of filler metals that appropriate with the metals to be welded. Due to dependence of the electrode to welding parameters, it is needed to known appropriate welding parameter and technique. Micro structure and chemical composition of the weld result are predicted on Schaeffler diagrams in addition to direct observation of mechanical testing and metallographic. Welding process is carried out with SMAW process. The maximum heat input that produced by the process is limited to 10 kJ/cm. Hadfield and carbon steel plate are machined to form the V-butt joint with weld specimen dimension 100 x 80 x 15 mm. To simulate tensile stress, ends of the weld joints are restraint. Weld specimens are divided into several part for mechanical testing and metallographic purposes. Micro Vicker\'s Hardness test result shows non-uniform distribution of hardness along weld area for using of combination E3 161, and E7018 electrodes. On the other hand, using of E307 electrodes do not show such behavior. Optical microscope observations produce some micro crack (fissure) on weld metal structure when using E316L+E7018 electrodes. Toughness on HAZ of Hadfield steel lower than weld metal and HAZ of carbon steel for E316L+E7018 electrodes.